(untitled) (Journal of International Relations and Peace, 2024)
Sudan has long been plagued by recurring conflicts rooted in ethnic, political, and economic grievances. Traditional top-down peace processes, led by national and international actors, have often failed to deliver sustainable peace. The Data Collection Primary data is collected through semi-structured interviews with key stakeholders, including local community leaders, grassroots activists, women’s groups, and youth organizations involved in peacebuilding, exploring grassroots approaches to peacebuilding in Sudan and focusing on local communities as drivers of sustainable conflict resolution. Examining the role of grassroots initiatives in promoting peace also highlights how localized efforts can address the root causes of conflict and foster social cohesion. Through case studies from diverse regions within Sudan, the study analyses the effectiveness of community-led interventions such as dialogue sessions, youth and women’s participation, and cultural practices in resolving conflicts. The findings underscore the importance of empowering local actors and integrating their knowledge and strategies into national peace efforts. The study contributes to the growing discourse on localized peacebuilding, offering insights that can inform policies to create lasting peace in Sudan and other conflict-affected regions.